Vertical agriculture: Suspended horticulture in towers - WorldFish (2014)
Suspending horticulture activities above the ground can result in high production of vegetables when the challenges of unfertile or saline soil, flooding, waterlogging, and land and water constraints are encountered. A vertical tower is a cylindrical structure made from bamboo, live wood, soil, coconut coir, brick chips, compost and cow manure for growing vegetables. The size and shape of the tower depends on the geographical location, land space, availability of resources, and intensity and height of waterlogging, flooding or salinity. The vertical tower allows for yearlong vegetable production in the homestead, where vegetables can grow on top of or within other structures, such as the roof of a house, nets or trees.